2016
DOI: 10.1073/pnas.1525637113
|View full text |Cite
|
Sign up to set email alerts
|

Human symbionts inject and neutralize antibacterial toxins to persist in the gut

Abstract: The human gut microbiome is a dynamic and densely populated microbial community that can provide important benefits to its host. Cooperation and competition for nutrients among its constituents only partially explain community composition and interpersonal variation. Notably, certain human-associated Bacteroidetes—one of two major phyla in the gut—also encode machinery for contact-dependent interbacterial antagonism, but its impact within gut microbial communities remains unknown. Here we report that prominent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
203
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(218 citation statements)
references
References 40 publications
11
203
0
Order By: Relevance
“…Through cycles of extension and contraction, this pathway delivers effector proteins from the cytoplasm of a donor bacterium directly into the periplasm or cytoplasm of a recipient bacterium (3,4). Used by both pathogenic and commensal bacteria of eukaryotes, the T6SS mediates a complex interplay of bacterial cell-cell interactions between beneficial and disease-causing bacteria (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Through cycles of extension and contraction, this pathway delivers effector proteins from the cytoplasm of a donor bacterium directly into the periplasm or cytoplasm of a recipient bacterium (3,4). Used by both pathogenic and commensal bacteria of eukaryotes, the T6SS mediates a complex interplay of bacterial cell-cell interactions between beneficial and disease-causing bacteria (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Each antibacterial effector can be neutralized by a genetically linked immunity protein that confers protection against effector delivery between sister cells (7,12,13). In addition, the T6SS has been shown to play an important role in vivo in multiple species, including human-symbiotic Bacteroidetes species (14)(15)(16). As a lethal weapon, the T6SS has been shown to mediate kin recognition in the multicellular bacterium Proteus mirabilis, which can develop elongated swarmer cells and form distinct boundaries (known as Dienes lines) between different P. mirabilis strains (17)(18)(19)(20).…”
mentioning
confidence: 99%
“…For instance, Kerr et al (2002) showed that E. coli strains coexist when interactions are spatially explicit, thus echoing theoretical work on the coexistence of species in structured communities (Hofbauer and Schreiber 2010;Mouquet and Loreau 2002). Indeed, experiments (in vivo or in vitro) of microbiome invasions, particularly those that combine them with ecological mathematical modelling (e.g., Stein et al 2013;Marino et al 2014;Wexler et al 2016), could help further probe the properties of the WH networks that make competitive interactions either effective or ineffective at preventing invasions.…”
Section: Competitive Interactions and Invasionsmentioning
confidence: 94%
“…are usually attributed to (i) their lowering of environmental pH through lactic acid production, (ii) their production of bacteriocins and other bacteriocidal compounds such as biosurfactant or hydrogen peroxide (H 2 O 2 ), and (iii) their competitive exclusion of other bacterial species (Boskey et al 2001;Fayol-Messaoudi et al 2005;Kaewsrichan et al 2006;Ling et al 2013;Ravel et al 2011). Similarly, a study on the persistence of human-associated Bacteroidetes in the gut (discussed earlier in Section 2.3) showed that some bacterial species can exclude an invader by producing bactericidal effectors triggered by direct physical contact, and that this activity is mediated by resistance evolution and relative population densities between species (Wexler et al 2016). Finally, how our commensal or mutualist viruses interact with each other or the microbiome in order to prevent invasions is significantly less understood.…”
Section: Resident Species Actively Prevent Invasionsmentioning
confidence: 99%
See 1 more Smart Citation